The influence of structural capital and knowledge management on the performance: The case study of Telekom Malaysia Headquarters - Mat Nor, Norzanah; Jamaludin Nor, Norlelawati (2008)
Due to the messy and complex challenges that are happening now,the current business environment cannot be predicted with relative ease.Many organizations including Telekom Malaysia Headquarters believe that, embarking into the knowledge economy is one of the best business strategies to making sure for the organization to survive in the very competitive and turbulent environment. Focusing on the usage of knowledge and intellectual capital have now become the most important agenda to many organizations.They believe that by managing and leveraging their intellectual capital, it will help to improve their immediate and long term business performance.However, the gap between the actual needs of those organizations as well as the theoretical and practicality part of it,is still missing.Therefore, this conceptual paper tries to investigate the influence of intellectual capital’s components specifically i.e. structural capital and knowledge management on the performance of Telekom Malaysia Headquarters.It consists of studying the impact of structural capital towards the practice of knowledge management in Telekom Malaysia Headquarters.Several specific issues such as the relationship between gender and education level, managerial expertise and organizational culture on structural capital as well as knowledge management practices will also be explored further.